THE STRUCTURAL BEHAVIOR OF COLD-FORMED STEEL HOLLOW STRUCTURAL SECTIONS UNDER UNIAXIAL BENDING - Budiman, Budiman; Al Hanif, Basit; Yuliansyah, Raka Mirza (International Journal of Civil Engineering and Infrastructure, 2024)
This study investigates the structural behavior of Cold-Formed Steel (CFS) Hollow Structural Sections (HSS) under uniaxial bending. Cold-formed steel is increasingly used in modern structural applications due to its material efficiency and ease of fabrication, though its bending response is not fully understood. The research combines numerical and experimental analyses to evaluate the bending performance of CFS HSS under uniaxial loading, considering various section sizes, wall thicknesses, and material properties such as yield strength and tensile strength. A finite element model was developed to simulate the bending behavior, focusing on the effects of section geometry and material characteristics. Experimental tests were conducted to validate the numerical model and provide empirical data on the bending capacity and failure modes. The results show that wall thickness and section geometry significantly influence the bending behavior, with thinner-walled sections being more susceptible to local buckling. Additionally, material strength plays a critical role in enhancing the bending capacity, with stronger materials resulting in higher load-carrying capacities. The findings of this study provide valuable insights into the design and application of CFS HSS, contributing to more accurate and reliable design codes for cold-formed steel structures.